Heart rate recovery after the 6‐min walk test is related to 6‐min walk distance and percutaneous oxygen saturation recovery in patients with COPD. Issue 4 (20th March 2015) - Shiroishi, Ryota; Kitagawa, Chika; Miyamoto, Naomi; Kakuno, Nao; Koyanagi, Harumi; Rikitomi, Naoto; Senjyu, Hideaki
<x xml:space="preserve">Abstract</x> Heart rate recovery (HRR) after maximal load exercise affects mortality in chronic obstructive pulmonary disease (COPD). However, the associations of clinical characteristics with HRR after the 6‐min walk test (6MWT), which is defined as a submaximal load test, remain unclear. We showed that HRR in patients with COPD after 6MWT was related to 6‐min walk distance and percutaneous oxygen saturation recovery. HRR after the 6MWT may be useful to assess exercise capacity in COPD.